Modelling the Okun’s Law in the midst of Structural Breaks: Evidence from Nigeria - Iyoboyi, Martins; Sabitu , Abubakar; Felix Okereke, Samuel (Journal of Indonesian Applied Economics, 2024)
Purpose This study aims to examine the relationship between economic growth and unemployment in Nigeria, specifically investigating the validity of Okun's law. Design/methodology/approach The study employs both linear and non-linear specifications using quarterly data from 1991Q1 to 2019Q1. Cointegration techniques that account for structural breaks are applied. Findings Unemployment and economic growth are found to be cointegrated. Both linear and non-linear specifications show a positive relationship between growth and unemployment, but the impact of unemployment on growth is not statistically significant. The study concludes that the growth experienced in Nigeria during the study period did not lead to reduced unemployment, thus invalidating Okun's law. Research limitations/implications The study's findings are based on data up to 2019Q1 and may not reflect more recent trends.  The analysis relies on the accuracy and reliability of the data sources used. Originality/value This study contributes to the understanding of the relationship between economic growth and unemployment in Nigeria, highlighting the need for policies targeting sectors with high employment potential.